Ultrasound elastography is a reproducible and feasible tool for the evaluation of the patellar tendon in healthy subjects. (29th November 2013) - Porta, F.; Damjanov, N.; Galluccio, F.; Iagnocco, A.; Matucci‐Cerinic, M.
Abstract Objective To evaluate the feasibility and reproducibility of ultrasound elastography (UE) in the assessment of healthy patellar tendon and to describe its UE pattern. Methods Twenty‐two patellar tendons of 11 out of 16 healthy subjects who met the inclusion criteria were evaluated three times by ultrasound (US) and UE at their proximal, middle and distal portions, by two separate sonographers with different experiences in UE. Results In all tendon portions the color map analysis showed a predominance of green (highly elastic), with good values of intra‐observer (Operator 1: P‐values = 0.790, 0.864, 0.865; Operator 2: P = 0.642, 0.882, 0.613 for proximal, middle and distal portions, respectively) and inter‐observer (P = 0.657) agreement. For both operators the intra‐observer analysis of the elasticity ratio (ER) between the tendon and the subcutis showed high agreement values (P < 0.001 for both operators). The inter‐observer analysis showed also high agreement values (P < 0.001 at proximal, P = 0.001 at middle, P = 0.005 at distal portions). The overall analysis of the ER of the tendon portions showed values of (mean ± SD): 1.47 ± 0.64, 4.38 ± 1.36, 3.32 ± 1.20 for proximal, middle and distal portions, respectively. The mean time to perform the UE evaluation for the inexperienced operator was 5 min at the beginning of the study but decreased to 2 min after a few examinations were done. The mean time for the expert was 2 min for the entire study. Conclusions UE is a feasible and reproducible tool for the evaluation of the healthy patellar tendon and further data are needed to define its role in the assessment of tendon pathology.